Earth like you've never seen it before: PRISMA reveals the state of our planet's health - Giuseppina Piccirilli (mediaGEO soc. coop., 2019)
Water quality, crops monitoring, drought and wildfire risk, air pollution: the Italian Space Agency started to release new images from the PRISMA satellite, which reveal the state of our planet's health and contributes to the United Nations Sustainable Development Goals. Thanks to its hyperspectral sensor, developed by Leonardo and the first of its kind ever launched in Europe, PRISMA proves to be a versatile guard to protect the environment.